Improving through‐thickness conductivity of carbon fiber reinforced polymer using carbon nanotube/polyethylenimine at the interlaminar region. Issue 5 (29th July 2020) - Robert, Colin; Thitasiri, Witiwat Best; Mamalis, Dimitrios; Hussein, Zakareya Elmo; Waqas, Muhammad; Ray, Dipa; Radacsi, Norbert; Koutsos, Vasileios
Abstract: The through‐thickness conductivity of carbon fiber reinforced polymer (CFRP) composite was increased by incorporating multiwalled carbon nanotubes in the interlaminar region. Carbon nanotubes (CNTs) were dispersed in a polyethylenimine (PEI) binder, which was then coated onto the carbon fiber fabric. Standard vacuum‐assisted resin infusion process was applied to fabricate the composite laminates. This modification technique aims to enhance the electrical conductivity in through‐thickness direction for the purpose of nondestructive testing, damage detection, and electromagnetic interference shielding. CNT concentrations ranging from 0 to 0.75 wt% were used and compared to pristine CFRP samples (reference). The through‐thickness conductivity of the CFRP exhibited an improvement of up to 781% by adopting this technique. However, the dispersion of CNT in PEI led to a viscosity increase and poor wetting properties which resulted in the formation of voids/defects, poor adhesion (as shown in scanning electron micrographs) and the deterioration of the mechanical properties as manifested by interlaminar shear strength and dynamic mechanical analysis measurements. Abstract :